THE UNSEEN: BURDEN IN CAREGIVERS OF PATIENTS WITH SCHIZOPHRENIA IN A TERTIARY CARE INSTITUTE - DEVALIYA, SANGEETA; TOMAR, SHASHI PRABHA; GUPTA, PREETI; SONI, VAISHALI; DHAKAR, JAGMOHAN SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: This study aims to evaluate the prevalence of caregiver burden in patients with schizophrenia using the burden assessment schedule (BAS). Methods: A cross-sectional study was conducted with 100 patients diagnosed with schizophrenia and their respective caregivers from the patients admitted in the male and female wards of the psychiatric department to evaluate caregiver burden. The BAS is used to determine the burden on caregivers of schizophrenic patients. Results: This study revealed that 51% of the caregivers had experienced moderate levels of burden. Older caregivers experienced a significantly higher burden (p=0.03), whereas residence and educational status had no significant effect on the burden. The burden was highest among parents, followed by spouses, and the burden is positively correlated with gender and older caregivers. Conclusion: It is evident that an unaddressed burden exists among the caregivers of patients who have mental illness. It is crucial to develop strategies to lessen the load of caregiving and implement them effectively. Counseling and psychological support, though they do not directly mitigate the suffering of patients, may help improve the quality of care given by them to individuals with schizophrenia, thus overall improving the mental well-being of the whole family.